Extraction of Cellulose Nanocrystals and Nanofibers from Rubber Leaves and Their Impacts on Natural Rubber Properties - Somphol, Wanasorn; Chanka, Napassorn; Boonmalert, Tanabadee; Loykulnant, Surapich; Prapainainar, Paweena; Seubsai, Anusorn; Dittanet, Peerapan (Applied Science and Engineering Progress, 2024)
This study aimed to chemically isolate two distinct types of nanocellulose derived from rubber leaves and investigate their use in natural rubber (NR). The cellulose nanocrystals (CNCs) were obtained through acid hydrolysis, while oxidation with 2, 2, 6, 6-tetramethylpiperidine-1-oxyl (TEMPO) was used to produce cellulose nanofibers (CNFs). The CNCs exhibited rigid and rod-like structures due to the removal of amorphous regions through acid hydrolysis, whereas the CNFs retained flexible, fiber-like morphologies and high aspect ratios. Incorporating CNCs or CNFs into NR improved its tensile properties, with the rigid CNCs enhancing the mechanical properties more than the flexible CNFs. CNC addition resulted in a 40% increase in tensile strength and a 38% increase in Young's modulus of NR. However, elongation at break decreased with filler content. On the other hand, CNF addition improved the elongation at the break without compromising the tensile properties. NR with CNF addition exhibited a 25% increase in tensile strength, a 30% increase in Young's modulus, and a 20% increase in elongation at break. Additionally, the biodegradability of NR nanocomposite films containing CNCs or CNFs surpassed that of unfilled NR film. Notably, a 6-month soil burial test revealed weight losses of 35% and 40% for NR nanocomposite films with CNCs and CNFs respectively, compared to a weight loss of 25% for the unfilled NR film.